2007
DOI: 10.1590/s0102-76382007000400022
|View full text |Cite
|
Sign up to set email alerts
|

Variáveis capnográficas pré e pós-tromboendarterectomias pulmonares

Abstract: In these case report, the results of late dead space fraction (fDlate), end-tidal alveolar dead space fraction (AVDSf), arterial-alveolar gradient CO2 [P(a-et)CO2], and slope phase 3 of spirogram of two patients who underwent thromboendarterectomy for pulmonary embolism (PE) are shown. PE was diagnosed by pulmonary scintigraphy, helical tomography, and pulmonary angiography. The calculation of fDlate, AVDSf and P(a-et)CO2 was based on volumetric capnography associated with arterial blood gas analysis. The pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…In the literature, we observe the following higher cut-off values for the studied variables: 0.15 for AVDSf,6 0.12 for fDlate,7 and 5 mmHg for P(a-et)CO 2 8. Considering the fact that a higher calculated value indicates greater obstruction of the vascular system (and a larger alveolar dead space), we infer that there is a correlation between the extent of the area without perfusion and the value obtained 35. In this patient, the result of VCap variations were displayed in imaging results.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the literature, we observe the following higher cut-off values for the studied variables: 0.15 for AVDSf,6 0.12 for fDlate,7 and 5 mmHg for P(a-et)CO 2 8. Considering the fact that a higher calculated value indicates greater obstruction of the vascular system (and a larger alveolar dead space), we infer that there is a correlation between the extent of the area without perfusion and the value obtained 35. In this patient, the result of VCap variations were displayed in imaging results.…”
Section: Discussionsupporting
confidence: 53%
“…The association of VCap variables with ABGA allows for the calculation of several indices, the variations of which can infer the presence of occlusion or improve after treatment of pulmonary vessels 35…”
Section: Case Reportmentioning
confidence: 99%
“… 8 - 11 In Revista Brasileira de Cirurgia Cardiovascular, different sections were found, for example: Special Article, Brief Communication, Clinical Surgical Correlation and Experience of the Service. 12 - 14 …”
Section: Discussionmentioning
confidence: 99%
“…This was due to the fact that the opening of the vascular beds by removal of thrombotic material resulted in great improvement of pulmonary perfusion and consequent reduction in the volume of alveolar dead space. Moreira and colleagues conducted two studies: one evaluating two capnography variables (AVDSf and fDlate) in a patient with chronic pulmonary hypertension due to exacerbation of PE,12 and another evaluating the same capnographic variables in two patients submitted to surgical embolectomy 9. The authors demonstrated that AVDSf and fDlate both correlated with the findings of imaging studies, their values moving closer to reference values as the imaging test results improved.…”
Section: Discussionmentioning
confidence: 99%